1992
DOI: 10.1103/revmodphys.64.441
|View full text |Cite
|
Sign up to set email alerts
|

Electron production in proton collisions with atoms and molecules: energy distributions

Abstract: All known data on the energy distribution of secondary electrons from collisions of protons with atoms and molecules have been reviewed and differential cross sections have been collected. The two experimental methods used to obtain the data are discussed and possible sources of error pointed out. Theoretical treatments are reviewed and several methods of checking the consistency of the data are discussed. Two semiempirical models have been chosen to represent the differential cross sections, and parameters fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
253
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(257 citation statements)
references
References 144 publications
4
253
0
Order By: Relevance
“…Rudd et al (1985Rudd et al ( , 1992 demonstrated that the present FBA-HF is reliable for calculating the SDCS integrated over ejected electron energy. Consequently, the integrated recoil spectrum and thereby subsequently all measured FDCS were normalized to 1.29 x 10 -17 cm 2 which is the FBA-HF results integrated over the same energy range.…”
Section: Resultsmentioning
confidence: 99%
“…Rudd et al (1985Rudd et al ( , 1992 demonstrated that the present FBA-HF is reliable for calculating the SDCS integrated over ejected electron energy. Consequently, the integrated recoil spectrum and thereby subsequently all measured FDCS were normalized to 1.29 x 10 -17 cm 2 which is the FBA-HF results integrated over the same energy range.…”
Section: Resultsmentioning
confidence: 99%
“…Using R n , x varies according to events of ion impact ionization. For the distribution for E e , we employ the Rudd model (Rudd et al, 1992) that almost reproduces this distribution in C 6+ ion impact ionization (Cappello et al, 2009, Ohsawa et al, 2013. We take the distribution for θ and φ to be isotropic (Moribayashi, 2014a(Moribayashi, , 2015a.…”
Section: The Explanation Of Procedures (Ii -V)mentioning
confidence: 99%
“…In addition, the cross section for charge transfer is negligible for protons of this energy. Ionisation interactions of those protons are treated in PTra by a semi-empirical model for the ionisation cross section developed by Rudd et al (1992), which is based on experimental data of water vapour. Secondary electron spectra resulting from those ionisations and their angular distribution are determined by the Hansen-Kocbach-Stolterfoht (HKS) model, which uses the semi-classical approximation (Bernal and Liendo, 2006;Hansen and Kocbach, 1989).…”
Section: Interaction Cross Section Data In Ptra and Geant4-dnamentioning
confidence: 99%
“…Investigations on the accuracy of using water to represent the DNA are currently being conducted at PTB . Due to the absence or unreliability of measured interaction cross sections in the condensed phase, track structure simulations generally utilise physical interaction cross sections for water that rely on measurements in water vapour, supplemented by extrapolations and theoretical models for condensed-phase effects (Dingfelder et al, 1998;Emfietzoglou and Nikjoo, 2005;Kutcher and Green, 1976;Rudd et al, 1992). The interaction between neighbouring molecules and the modification of the inter-and intra-molecular structure lead to significant changes of interaction cross sections, to energy shifts and a reduced amplitude of vibrational excitations as well as to additional collective modes of energy loss in the condensed phase compared to the gas phase (Michaud et al, 2003;Sanche et al, 1995).…”
Section: Introductionmentioning
confidence: 99%